2003
DOI: 10.1074/jbc.m212488200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor SREBP-1c Is Instrumental in the Development of औ-Cell Dysfunction

Abstract: We also found that the SREBP-1c processing in ␤-cells was irresponsive to acute stimulation of glucose and insulin, which was distinct from that in lipogenic tissues. However, 2-day exposure to these agents promoted SREBP-1c processing. Therefore, the SREBP-1c maturation could be implicated in the pathogenesis of ␤-cell glucolipotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
75
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 75 publications
13
75
5
Order By: Relevance
“…We [93,94] and others [95,96] have recently shown that elevations of beta cell triglyceride content caused by overexpression of the lipogenic transcription factor sterol regulatory element binding protein (SREBP1c) leads to a substantial accumulation of intracellular lipid and the near-complete elimination of both phases of glucose-stimulated insulin secretion from beta cells and islets, consistent with reports of inhibitory effects on insulin secretion of lipid infusion in vivo [97] and the culture of islets with fatty acids in vitro [98]. The effects of SREBP1c overexpression are associated with decreased glucose-induced increases in cytosolic [ATP], vesicle motility at both low and high glucose concentrations, and a reduction in the number of glucose-stimulated release events [99] (Fig.…”
Section: Glucose-stimulated Insulin Secretion Is Biphasic: Visualisatmentioning
confidence: 88%
“…We [93,94] and others [95,96] have recently shown that elevations of beta cell triglyceride content caused by overexpression of the lipogenic transcription factor sterol regulatory element binding protein (SREBP1c) leads to a substantial accumulation of intracellular lipid and the near-complete elimination of both phases of glucose-stimulated insulin secretion from beta cells and islets, consistent with reports of inhibitory effects on insulin secretion of lipid infusion in vivo [97] and the culture of islets with fatty acids in vitro [98]. The effects of SREBP1c overexpression are associated with decreased glucose-induced increases in cytosolic [ATP], vesicle motility at both low and high glucose concentrations, and a reduction in the number of glucose-stimulated release events [99] (Fig.…”
Section: Glucose-stimulated Insulin Secretion Is Biphasic: Visualisatmentioning
confidence: 88%
“…In ␤-cells, chronic highglucose treatment increases the nuclear form of ADD1/ SREBP1c, a process involving proteolytic cleavage and nuclear translocation (10,11). In addition, ectopic overexpression of mature ADD1/SREBP1c has been shown to increase intracellular lipid deposition and therefore to hinder glucose-stimulated insulin secretion (GSIS) and stimulate ␤-cell apoptosis (12,13).…”
mentioning
confidence: 99%
“…The activation of SREBP-1c causes ␤ cell dysfunction, including impaired insulin expression and secretion in vitro (INS-1 cells) and in vivo (transgenic mice) (22,27). In both cases, reduction of PDX-1 was observed and was thought to contribute to ␤ cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…overexpression in ␤ cells caused impaired insulin secretion, suppression of insulin and pdx-1 expression, and reduction of ␤ cell mass (22,27). Next, we explored the effect of SREBP-1c on the Pdx-1 promoter.…”
Section: Srebp-1c Suppresses the Endogenous Activity Of Pdx-1 In ␤ Cementioning
confidence: 99%
See 1 more Smart Citation